2022
DOI: 10.3389/fresc.2022.856904
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Thermal Demands and Mobility Performance During International Wheelchair Rugby Competition

Abstract: ObjectiveTo determine the thermoregulatory responses and mobility performance of wheelchair rugby (WCR) players during international competition.MethodsEleven male National Team WCR players volunteered for the study. Testing occurred during a four game series against international competition (temp 24.7 ± 0.7°C, relative humidity 50.1 ± 3.6%), with movement time (MT) and gastrointestinal temperature (Tgi) recorded continuously.ResultsThe mean maximal Tgi was 38.6 ± 0.6°C (37.9–39.7) and did not significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Whereas the field test duration was fixed at 32 min, the time the players were in movement seemed to be higher in the real games (median: 39.5 IQR: 28.7 min, range: 22:17–66:13 min). Additionally, Gavel et al [ 22 ] observed a large variability in overall movement time (27:43 ± 9:40 min (range: 12:10–43:10)) during a WCR game. Since WCR players also remain active when the game clock was stopped the duration was longer than the effective playing time.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the field test duration was fixed at 32 min, the time the players were in movement seemed to be higher in the real games (median: 39.5 IQR: 28.7 min, range: 22:17–66:13 min). Additionally, Gavel et al [ 22 ] observed a large variability in overall movement time (27:43 ± 9:40 min (range: 12:10–43:10)) during a WCR game. Since WCR players also remain active when the game clock was stopped the duration was longer than the effective playing time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, differences in environmental conditions and test protocols could also explain the discrepancy between our results and the maximum velocities observed during matches. In addition to the impact of the floor covering, factors such as temperature and humidity can also affect player performance during a match ( 23 ).…”
Section: Discussionmentioning
confidence: 99%